H.P. Intertrading Company Limited: Think of furniture materials, think of H.P. Intertrading - Chatkaewmanikun, Racha (2016)
The purpose of this business plan is to reinvigorate and sustain the family business as furniture material intermediary, called ‘H.P. Intertrading’. The plan will be implemented from 2017 to 2019.